Pharmacological Vunerability of Chemophoric Groups - Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2022)
The drugs target the pathological proteins for the pharmacological intervention through their vunerability of chemophoric and congate groups 1-3 at therapeutic level. They are essential for binding affinity, intrinsic efficacy and bioavailability. They are introduced in bioactive molecules by replacement of hydrogen atoms. They are implicated in SAR modifications and interactional participation with receptor or enzyme or target protein. The pharmacological influence of them is delineated here.